Community health workers and social change:. Issue 1 (May 2015) - MAES, KENNETH; Maes, Kenneth
<x xml:space="preserve">Abstract</x> Major global health institutions, public and private, currently see community health workers (CHWs) as crucial resources. But the daily experiences and complex motives of CHWs, as well as their concerns and criticisms, remain poorly understood by the institutions that promote their value and draw on their labor. Donors, states, NGOs, and other public health institutions often approach the motivations and performance of CHWs as problems that can be solved with a mix of psychological, economic, and management theories; novel incentive packages and supervisory structures; and surveys, interviews, and randomized controlled trials. This special issue shifts the goal toward documenting power inequalities, labor relations, and interactions among CHWs, donors, health officials, supervisors, and care recipients. The articles in this issue offer valuable ethnographic accounts of CHWs in 21st‐century Africa, Latin America, and Asia, and deliver a clear message: CHWs participate in important relationships and politics, seeking change in their own job conditions and roles, and other social, political, and economic changes. These forms of "participation" are variable, evolving, and shaped by unique local histories as well as transnational policies and norms. The articles here aim to demonstrate that ethnography and mixed methods can help bring about improvements in policy and practice by explaining and interpreting CHW practices and governance and by encouraging global health actors to treat CHWs not as magic bullets or human resources, but as people with multiple skills, desires, and perspectives.